Performance and Carcass Characteristics of Broiler Chickens Fed Diets Supplemented with Graded Levels of Roxazyme G® - Omojola, A.B.; Adesehinwa, A.O.K. (International Journal of Poultry Science, 2007)
The use of exogenous enzymes as feed additives is still undergoing a lot of research. A total of three hundred and sixty unsexed three week-old Abor Acre plus strain broiler chicken were randomly allocated to four experimental dietary treatments in a completely randomized design to evaluate the effect of Roxazyme® on performance and carcass characteristics of broiler chickens. The diets 1, 2, 3, and 4 contained 0, 0.1, 0.2 and 0.3% enzyme supplementation respectively. The birds were fed the experimental diets for a 35-day period during which data were obtained on feed intake, weight gain, dry matter digestibility (DMD) and feed conversion ratio. At the end of the feeding trial, ten birds were sacrificed per replicate to evaluate carcass and meat characteristics. The inclusion of the exogenous enzyme did not significantly (P>0.05) improve the average weight gain, feed intake, feed conversion ratio and DMD. The dressing percentage of birds fed the enzyme-supplemented diets was significantly (P